PELAKSANAAN KONSINYASI DALAM KEGIATAN PENGADAAN TANAH BAGI PEMBANGUNAN JALAN TOL PANDAAN-MALANG ( STUDI DI DESA CAPANG, KECAMATAN PURWODADI, KABUPATEN - VASKAL BENOVEN TAMBUNAN (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
The case of land acquisition for public interest is common in Indonesia in general, and especially in Pasuruan regency, ie. land for the interest of the Pandaan-Malang toll road section. It is an interesting case study as this issue becomes the basis of the wider community. This study entitles Implementation of Consignment in Land Acquisition Activities for Toll Road Development of Pandaan-Malang: Study in Capang Village, Purwodadi District, Pasuruan Regency. The objective of the research are to reveal (1) the Apprasial process in determining the compensation of the valuation of the party in the consignment Based on Fairness Value in the Village Capang, and (2) the inhibiting factors in the implementation process of Land Procurement for Public Interest so that the Consignment process occurred. To overcome these obstacles, three ways are done, namely (a) consultation with the community; the district court; And the Supreme Court. However, if these three ways still can not solve the problems, then the next way is to consign. To get compensation that satisfies the sense of sustainability justice, it is advisable to compensate not in the form of money, but in the form of shares in accordance with one of the mandates of Law No. 2 year of 2012 where it is stated that the Government should not act authoritatively in the procurement of land, even for the public interest, to pay attention to the rights and origins of local land. Keywords: Land Procurement, Public Interest, Consignment.